TRANSFORMASI PENDIDIKAN ISLAM DALAM CENGKERAMAN KEKUASAAN ORDE BARU - Handayani, Desika; Khori, Qolbi (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
This study aims to examine the dynamics of changes in Islamic education in Indonesia during the New Order era, especially in the context of its position and recognition in the national education system. Before the New Order, Islamic educational institutions such as Islamic boarding schools and madrasahs were in a marginal position and had not been fully recognized, so that public interest in Islamic education was relatively low. Using a narrative descriptive approach, this study analyzes how the New Order government's policies influenced the growth and development of Islamic educational institutions. During that period, Islamic education developed under tight control and ideological pressure, so that it had to make various concessions to the secular and bureaucratic national education system. However, Islamic education gradually underwent a transformation, from an isolated condition to limited recognition, although it remained under political and ideological supervision. Islamic educational institutions began to show resilience and adaptability, and succeeded in laying the foundation for a greater transformation after the Reformation era. The results of this study indicate that despite facing challenges and limitations, Islamic madrasahs, Islamic boarding schools, and universities were able to survive, develop, and make significant contributions to national development. ABSTRAKPenelitian ini bertujuan untuk mengkaji dinamika perubahan pendidikan Islam di Indonesia selama masa Orde Baru, khususnya dalam konteks posisi dan pengakuannya dalam sistem pendidikan nasional. Sebelum Orde Baru, lembaga pendidikan Islam seperti pesantren dan madrasah berada di posisi pinggiran dan belum diakui secara penuh, sehingga minat masyarakat terhadap pendidikan Islam relatif rendah. Dengan pendekatan deskriptif naratif, penelitian ini menganalisis bagaimana kebijakan pemerintah Orde Baru mempengaruhi pertumbuhan dan perkembangan institusi pendidikan Islam. Selama masa tersebut, pendidikan Islam berkembang di bawah kontrol ketat dan tekanan ideologis, sehingga harus melakukan berbagai konsesi terhadap sistem pendidikan nasional yang sekuler dan birokratis. Meski demikian, secara bertahap pendidikan Islam mengalami transformasi, dari kondisi terisolasi menuju pengakuan terbatas, walaupun tetap berada dalam pengawasan politik dan ideologis. Lembaga-lembaga pendidikan Islam mulai menunjukkan ketahanan dan kemampuan beradaptasi, serta berhasil meletakkan fondasi bagi transformasi yang lebih besar setelah era Reformasi. Hasil penelitian ini menunjukkan bahwa meskipun dihadapkan pada tantangan dan keterbatasan, madrasah, pesantren, dan perguruan tinggi Islam mampu bertahan, berkembang, dan memberikan kontribusi signifikan terhadap pembangunan bangsa.